Legal Study On Land Ownership Rights Of Indonesian Citizens As A Result Of Mixed Marriages (Case Study Of Constitutional Court Decision No. 69/Puu/Xiii/2015) - Dhanna Asha Audria Budi; R. Ismala Dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Mixed marriages in Indonesia often lead to legal complications, one of which concerns the commingling of assets that results in the erosion of the land ownership rights of Indonesian citizens (WNI). This issue arose because, prior to the issuance of Constitutional Court Decision No. 69/PUU-XIII/2015, the prevailing regulations did not allow WNI to enter into a prenuptial agreement after the marriage had taken place. Notably, not everyone understands the legal consequences of mixed marriages, which may lead to the absence of a prenuptial agreement before marriage. With the issuance of Constitutional Court Decision No. 69/PUU-XIII/2015, it is now possible to create a postnuptial agreement after the marriage has been solemnized. The purpose of this study is to analyze the issues surrounding land ownership rights arising in mixed marriages in Indonesia and to explore the solutions developed to achieve justice for all WNI without exception. The research employs a normative juridical or doctrinal approach, relying on secondary or library- based data. The findings indicate that the provisions on land ownership for WNI in. mixed marriages prior to the Constitutional Court Decision No. 69/PUU-XIII/2015 triggered significant controversy, as they were perceived as inconsistent with the principles of justice for WNI, particularly those engaged in mixed marriages without a prenuptial agreement. Following this decision, the regulations concerning marital agreements in mixed marriages were amended, allowing for the execution of postnuptial agreements. This development provides a viable solution to the issues of joint property in mixed marriages for those who had not entered into a prenuptial agreement before marriage, thereby fostering justice for all WNI.